CRITICAL REVIEW ON THE ROLE OF RADIOLOGY NURSES IN PERFORMING AND INTERPRETING DIAGNOSTIC TESTS. - Sahal Salem AbdullahLasloom, Ibrahim Saad Al Mordef, Mana Saad Al murdif, Mohamed Abdullah Askar Lasloom, Yosef Abdullah askarlasloom, Awadsaleh Ali lasloom, Saeed salehAlabas, Abdallah HadyNaserAllsloom (Chelonian Research Foundation, 2023)
Radiologists are critical in healthcare, particularly in performing and deciphering therapeutic examinations. This basic audit investigates the different parts of radiologists within the symptomatic handle and highlights their significance in quiet care and results. Key zones examined incorporate modest planning, procedural back, picture translation, and their part in collaboration with other doctors. This article summarizes the existing writing and analyzes the effect of radiologists on demonstrative precision, persistent security, and general care. In expansion, recommendations were made to move forward the part of radiologists in expressive services. Keywords: Radiology nurses, Diagnostic tests, Imaging procedures, Patient care, Interpretation